The Effectiveness of Pop-Up Book Learning Media in Enhancing Students Learning Outcomes in History on European Events Influencing Human Life at SMA Negeri 12 Ambon - Kristina Loru; Endang Endang; Marjhersty Dwiana Tiwery; Agustinus Ufie; Jenny Koce Matitaputty (Universitas Syiah Kuala, 2022)
This study aims to examine the effectiveness of using Pop-Up Book learning media in improving student learning outcomes on the topic of Events in Europe that Influenced Human Life in Grade XI at SMA Negeri 12 Ambon. The background of this research is based on the importance of mastering historical materials, which are often difficult for students to understand without the support of engaging, visual, and interactive learning media. The research method used is Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results showed that the use of Pop-Up Book media significantly improved student learning outcomes. In the initial test, only a small portion of students reached the Minimum Competency Criteria (KKM). After the first cycle, classical completeness increased significantly, and by the second cycle, most students had met or exceeded the KKM. The cooperative learning approach applied during the lessons also encouraged active student interaction, enhanced understanding of historical material, critical thinking skills, and collaboration. Based on these findings, Pop-Up Book media can be recommended as an innovative alternative in history learning at the senior high school level